AI and humanistic management : aesthetics in managerial theory and practice - Szostak, Micha?? (Routledge, 2026)
This book, situated at the intersection of humanistic management, aesthetics, and artificial intelligence (AI) studies, aims to explore how the emergence of AI-driven solutions reshapes managerial paradigms, alters human experiences within organisations, and redefines the values guiding leadership, communication, and organisational development. By adopting a cross-disciplinary and multi-paradigmatic perspective, the volume seeks not only to identify the opportunities AI presents for enhancing human dignity and creativity at work but also to critically examine the risks of dehumanisation, aesthetic homogenisation, and ethical displacement. In the contemporary discourse on management theory and practice, the accelerated integration of AI technologies has initiated profound transformations that challenge the traditional humanistic foundations of organisational life. While AI is often perceived primarily through the lens of operational efficiency, cost optimisation, and decision-making enhancement, it also raises fundamental questions about the aesthetic, ethical, and relational dimensions of management. In this context, the book's critical research problem was formulated in the following manner: understanding how AI-driven aesthetics influence the humanistic character of management, under what conditions AI can serve human-centred goals rather than eroding them, and what long-term consequences AI integration may have for the emotional, ethical, and aesthetic dimensions of organisational life. Addressing these issues is essential for developing management practices that harmonise technological advancement with the humanistic values of autonomy, authenticity, empathy, and aesthetic experience.
Keywords: Artificial intelligence -- Philosophy.; Industrial management.; Artificial Intelligence; AI; Humanistic Management; Management Aesthetics; Organizational Change; Workplace Automation; Business Ethics; AI and Leadership; Critical Management Studies; Human-Centered AI; Future of Work; elektronické knihy; electronic books